Iman Besar Dalam Tubuh Mungil: Kajian Hermeneutik Kritik Historis Markus 10:13-16 dan Implementasinya Terhadap pelayanan Anak di Jemaat GMIM Eben Haezer Buntong - Ryanto Adilang (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2023)
Children are an integral part of the process of human development and growth. Before someone enters the adult phase, he will first go through childhood. This then obliges the church to also give attention and service to not only adults, but also children. Traditional child services are part of the duties and responsibilities of the faith. The church as a collection of believers really needs to respond to this as part of the noble call of duty before God. The qualitative research method was set to be the scalpel in this study. The research approach that is considered appropriate is a descriptive research approach equipped with historical criticism as a method for interpreting biblical texts. Historical criticism is a method of interpretation that considers historical elements as material for viewing and analyzing texts. It is hoped that this research will provide constructive results for children's ministry in contemporary churches, especially in the Evangelical Christian Church in Minahasa. In addition, the results of this study will also provide a paradigm update for child servants and parents in serving Christian children.